Fusarium mycotoxins: a trans-disciplinary overview. Issue 2 (3rd April 2018) - Bakker, Matthew G.; Brown, Daren W.; Kelly, Amy C.; Kim, Hye-Seon; Kurtzman, Cletus P.; Mccormick, Susan P.; O'Donnell, Kerry L.; Proctor, Robert H.; Vaughan, Martha M.; Ward, Todd J.
Abstract: Due to health risks and economic losses associated with mycotoxins produced by Fusarium species, there is a compelling need for an improved understanding of these fungi from across diverse perspectives and disciplinary approaches. In this article, we provide a transdisciplinary overview of: (i) Fusarium phylogenetics; (ii) linkages between mycotoxin biosynthetic gene clusters and chemical structures; (iii) biotransformation of mycotoxins to reduce toxicity; (iv) Fusarium population biology; (v) genomics of secondary metabolite production; and (vi) mycotoxigenic fusaria in a phytobiomes context. Phylogenetic studies have made tremendous progress in delineating the species that comprise the genus Fusarium, many of which are morphologically cryptic. Accurate species identification and a thorough understanding of the distribution of mycotoxin biosynthetic genes among those species will facilitate control of mycotoxin contamination. The biochemical pathways leading to the formation of several Fusarium mycotoxins have been elegantly linked with the genes responsible for each chemical transformation during synthesis, and for most structural differences among chemotypes. Screens for the biotransformation of mycotoxins have led to the description of chemical modifications that impact bioactivity and have implications for monitoring and testing of the food supply. Population biology studies have revealed the potential for introductions of foreign genotypes to alter regional populations of mycotoxigenic fusaria. Genomic analyses have begun to reveal the complex evolutionary history of the genes responsible for mycotoxin production, both across and within lineages. Improved understanding of how climate variability impacts plant– Fusarium interactions and mycotoxin accumulation is necessary for effective plant resistance. Additionally, improved understanding of interactions between Fusarium and other members of crop microbiomes is expected to produce novel strategies for limiting disease and mycotoxin accumulation.